2009
DOI: 10.1177/0143034309107080
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Adolescents’ Locus of Control and Healthy Dietary Behaviours and its Implications for School Psychologists and Other Health Related Professionals

Abstract: The Concept of Health Locus of Control (HLOC) indicates the personal belief of an individual about who or what affects his/her health. This approach emphasizes the importance of individual responsibility for health, especially in the school years which represent a 'critical period' for students to adopt healthy behaviours and lifestyles. The main aim of this survey is to define relationships between Health Locus of Control and the dietary behaviours of Turkish adolescent students by evaluating their risky heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Tabak et al (2009) found that primary and secondary students with high internal-HLOC were more likely to adhere to a healthy diet, whereas those who believed that their adherence to a healthy diet was merely a matter of chance or fate (external-HLOC) displayed considerably more unhealthy eating behaviours. Some young people believe their health is in the hands of powerful others (such as parents), and for them, a healthy diet is dependent on their environment (Tabak et al, 2009). An internal locus of control is related to self-efficacy but includes an element of self-responsibility.…”
Section: Theoretical Views On Dietmentioning
confidence: 92%
See 2 more Smart Citations
“…Tabak et al (2009) found that primary and secondary students with high internal-HLOC were more likely to adhere to a healthy diet, whereas those who believed that their adherence to a healthy diet was merely a matter of chance or fate (external-HLOC) displayed considerably more unhealthy eating behaviours. Some young people believe their health is in the hands of powerful others (such as parents), and for them, a healthy diet is dependent on their environment (Tabak et al, 2009). An internal locus of control is related to self-efficacy but includes an element of self-responsibility.…”
Section: Theoretical Views On Dietmentioning
confidence: 92%
“…Habits and preferences are formed early and continue into later life (Birch, 1999), so it is important to establish healthy preferences as early as possible (Deshpande, Basil, & Basil, 2009). A healthy diet is necessary for healthy physical and mental development during childhood and adolescence (Jacka et al, 2010;Tabak, Piyal, Çelen, Karakoç, & Özen, 2009;Tomlinson, Wilkinson, & Wilkinson, 2009), and poor diet has recently been shown to have a more direct (i.e. biological) relationship with the development of psychological problems than previously thought (Jacka et al, 2010).…”
Section: Adolescents and Dietmentioning
confidence: 99%
See 1 more Smart Citation
“…Adolescents with high internal HLOC tend to consume healthier diets than those with external HLOC beliefs (Hayes & Ross, 1987;Tabak et al, 2009). Self-management programming can help school psychologists to promote a feeling of control within older children and adolescents; this may improve HLOC and health behaviors that influence risk factors for MetS and obesity.…”
Section: Implications For School Psychologistsmentioning
confidence: 99%
“…However, reviews in terms of predictive utility have been mixed (Luszczynska & Schwarzer, 2005). Chance health locus of control has been found to correlate to negative health behaviors, including alcohol consumption (Steptoe & Wardle, 2001), substance misuse (Haynes & Ayliffe, 1991), unhealthy nutritional habits (Tabak, Piyal, Ç elen, Karakoç, &Özen, 2009), smoking (Bennett, Norman, Moore, Murphy, & Tudor-Smith, 1997;Eiser et al, 1989;Steptoe & Wardle, 2001), and depression (Afifi, 2007).…”
Section: Cigarette Smoking and Lgbt Minority Stressmentioning
confidence: 99%